A novel single‐feed filtering dielectric resonator antenna using slotline‐loaded coupling structure. Issue 4 (21st January 2022) - Wang, Chuanyun; Zhang, Yonghua; Han, Zhiwen; Chen, Guibin; Guan, Xuehui; Ren, Baoping
Abstract: This paper proposes a novel single‐feed filtering dielectric resonator antenna (FDRA) using fusion design method and the microstrip‐slot coupled feeding structure. Two pairs of slotlines are elaborately designed and perpendicularly loaded on the coupling slot to provide two radiation nulls at the edges of the passband. Therefore, a compact DRA with a quasi‐elliptic function bandpass response is constructed without extra filter circuits. Furthermore, two radiation nulls can be individually controlled through changing the length of the corresponding slotlines. For proving the effectiveness of the design, a prototype FDRA operation at 3.45 GHz is fabricated and measured. The measured results show that the peak realized gain is 5.84 dBi and the ‐10dB impedance bandwidth is 10.29% (3.29 ‐ 3.65 GHz). The proposed FDRA not only has good performance, but also has simple design.